Food in Time and Place: The American Historical Association Companion to Food History - Paul Freedman, Joyce E. Chaplin, and Ken Albala (University of California Press, 2014)
One expression of the recent surge of interest in the history of food is the appearance of many more books and essays on the subject than were available just a few years ago. The small number of large books surveying food history in a general way has now been supplemented by both more ambitious and more specialized works: multivolume treatments across an extensive chronology, studies of food history as part of the interdisciplinary fi eld of food studies, even accounts of the historiography of food.1 The purpose of the present book is somewhat different and twofold: fi rst, to provide a convenient handbook presenting a geographically, chronologically, and topically broad range of food history, and second, to serve as a resource for teachers of food history, including those who are thinking about putting together such a course, those who have already taught one, and historians who would like to add or increase a food component in courses oriented towards one nation (e.g., French history), period (e.g., medieval history), or topic (e.g., history of immigration). This preface outlines the situation of a fi eld that can no longer be described as â€œemerging,â€ but that has achieved visibility and widely acknowledged importance. Here we want to suggest some aspects of the current situation of food history and look at how chapters in this book can contribute to its stated purpose.